I survived : the battle of D-Day, 1944 - Ball, Georgia (I survived (Graphic novel series), 2024)
With his French village under Nazi control, Paul Colbert joins a secret resistance after rescuing an American paratrooper and gets his chance to make a difference in the midst of the largest invasion in history, working to do his part in turning horror into hope.